A comparative analysis of the results obtained at the Olympic Games in women`s artistic gymnastics, 1988-2000 - Sterkowicz-Przybycien, K. (Human Movement, 2004)
Purpose. The aim of the present work was to compare and analyze the average results obtained by women artistic gymnasts and to discover some result patterns in the all-around individual competitions.